Management of acute stroke and urgent neurointerventional procedures during COVID-19 pandemic: recommendations on the Scientific Department on Cerebrovascular Diseases of the Brazilian Academy of Neurology, Brazilian Society of Cerebrovascular Diseases and Brazilian Society of Neuroradiology - Arruda Mont'alverne, Francisco Jose; Lima, Fabricio Oliveira; Nogueira, Raul Gomes; Macedo de Freitas, Carlos Clayton [UNESP]; Pontes Neto, Octavio Marques; Silva, Gisele Sampaio; Oliveira, Maura Salaroli de; Frudit, Michel; Mendes Pereira Caldas, Jose Guilherme; Abud, Daniel Giansante; Conforto, Adriana Bastos; Maia Carvalho, Fernanda Martins; et al. (Assoc Arquivos Neuro- Psiquiatria, 2020)
Introduction: Although the 2019 severe acute respiratory syndrome coronavirus 2 infection (SARS-CoV-2, COVID-19) pandemic poses new challenges to the healthcare system to provide support for thousands of patients, there is special concern about common medical emergencies, such as stroke, that will continue to occur and will require adequate treatment. The allocation of both material and human resources to fight the pandemic cannot overshadow the care for acute stroke, a time-sensitive emergency that with an inefficient treatment will further increase mortality and long-term disability. Objective: This paper summarizes the recommendations from the Scientific Department on Cerebrovascular Diseases of the Brazilian Academy of Neurology, the Brazilian Society of Cerebrovascular Diseases and the Brazilian Society of Neuroradiology for management of acute stroke and urgent neuro-interventional procedures during the COVID-19 pandemic, including proper use of screening tools, personal protective equipment (for patients and health professionals), and patient allocation.
Keywords: neurointerventional treatment; coronavirus infections; stroke